KARAKTERISTIK METASTASIS SISTEM SARAF PUSAT DARI KANKER PARU - Tan Yosephine; Tiara Aninditha; Henry Riyanto Sofyan; Jonathan Odilo; Rini Andriani (PERDOSNI, 2020)
Introduction: As much as 40% of lung cancer patients will experience central nervous system (CNS) metastasis in the course of the disease. From those 40%, as much as 3-9% will experience leptomeningeal metastasis, but the clinical profile of CNS involvement in lung cancer has never been studied before in Indonesia. Aim: To give a description of CNS metastasis from lung cancer inCipto Mangunkusumo General Hospital and National Cancer Referral Dharmais Hospital. Methods: This is a cross-sectional study done in patients consulted to Neurology Department inCipto Mangunkusumo General Hospital and National Cancer Referral Dharmais Hospital in 2018. Inclusion cirteria is adult patients diagnosed with lung cancer based on histopathology with complete medical record to the extent of CT scan or Head MRI with contrast. Results: There were 48 subjects with median age of 57 (36-76) years, men were more than women (56.2% vs 44.8%) and 31.3% had history of smoking. The most frequent lung cancer type is non-small cell lung cancer (NSCLC) (93,8%). Neurological symptoms found were motoric deficits (62.5%), headache (43.8%), cognitive dysfunction (20.8%), and seizure (18.8%). Majority of subjects suffered from brain metastasis (93.8%) and 8.3% were leptomeningeal metastasis. Discussion: The majority of CNS metastasis were brain metastasis from NSCLC (93.8%) with main neurological deficits were motoric deficits (62.5%) and headache (43.8%). Keywords: Brain metastasis, lung cancer, non-small cell lung carcinoma